2021
DOI: 10.3390/app112411892
|View full text |Cite
|
Sign up to set email alerts
|

Features of Acoustic Emission in Tensile Testing of Dissimilar Welded Joints of Pearlitic and Austenitic Steels

Abstract: This paper presents a study of acoustic emission (AE) during the deformation of dissimilar welded joints of austenitic steel to pearlitic steel. One of the specific problems in these welded joints is the presence of decarburized and carbide diffusion interlayers, which intensively increase in width during long-term high-temperature operation. The presence of wide interlayers negatively affects the mechanical properties of welded joints. Moreover, welded defects are difficult to diagnose in welded joints contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Moreover, an additional maximum of the AE hit rate appeared in the specimen with interlayers under static tension at such loads. In addition, such an AE waveform was detected during tension of dissimilar welded joints with diffusion interlayers in [22].…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Moreover, an additional maximum of the AE hit rate appeared in the specimen with interlayers under static tension at such loads. In addition, such an AE waveform was detected during tension of dissimilar welded joints with diffusion interlayers in [22].…”
Section: Discussionmentioning
confidence: 95%
“…It is advisable to start with considering patterns of AE data recorded under static loading (described in detail in [22]) to gain deep knowledge and understanding of AE data parameters under cyclic loading. Figure 4 shows the AE data obtained under static tension of a specimen without interlayers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Danielewski et al [8] conducted metallographic analysis of the weld and found that in stainless steel, the heat-afected zone was very narrow, and the growth of austenite grains was not observed, while the slender grains of ferrite formed a discontinuous network around the austenite grain. Another problem with dissimilar steel welds between austenitic steel and pearlitic steel is the presence of decarburization and carbide interlayers, which have an adverse efect on the mechanical properties of the welding seam [9]. Nikulina et al [10] studied the fash butt welding of high-carbon pearlitic steel and chromium-nickel austenitic steel, and the results showed that layered pearlite colonies containing chromium and nickel and thin austenite interlayers were formed in the weld zone.…”
Section: Introductionmentioning
confidence: 99%
“…Hempel [19] conducted an in-depth study on the residual stress state of dissimilar steel welds using X-ray and neutron difraction and confrmed that the residual stress on the surface of austenitic tubes during sample preparation was greatly afected by the machining technology. Barat et al [9] experimentally confrmed that the acoustic emission method can be used to detect both typical welding defects in welded joints of diferent structural grades of steel as well as difusion interlayers. Lyubimova et al [20] proposed that the combination of X-ray fuorescence analysis, X-ray difraction, and microhardness determination with traditional inspection methods (visual or ultrasonic inspection [21], etc.)…”
Section: Introductionmentioning
confidence: 99%